Geological development of and nature of fractures in the sleeted Dyke complex of the Spilia-Politiko area, Troodos ophiolite, Cyprus: implications for permeablity in oceanic crust - Van Everdingen, David Allard (1993)
Thesis (Ph.D.)--Memorial University of Newfoundland, 1993. Earth Sciences Bibliography: leaves [264]-285.